2022
DOI: 10.1108/ijlss-02-2022-0027
|View full text |Cite
|
Sign up to set email alerts
|

Lean construction and resilience while coping with the COVID-19 pandemic: an analysis of construction companies in Brazil

Abstract: Purpose Despite the benefits provided by the implementation of the lean philosophy, the most recent research discusses whether the high degrees of efficiency obtained with the implementation this philosophy could contribute positively or negatively in current pandemic scenario. This study aims to analyze how resilient construction industry companies in Brazil were in the face of the COVID-19 pandemic, comparing the performance of construction companies with different implementation levels of lean construction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…It focused on the workfrom-home impact due to social distancing during the pandemic in India's service industry. (Oey and Lim, 2021;Evans et al, 2022;Le and Nguyen, 2022;Evans and Farrell, 2023;Wu et al, 2023;Sari et al, 2023;Jiang et al, 2023;Simeão and Ferreira, 2023) 5 4 1 5…”
Section: Current Literature On Lean and Covid-19mentioning
confidence: 99%
“…It focused on the workfrom-home impact due to social distancing during the pandemic in India's service industry. (Oey and Lim, 2021;Evans et al, 2022;Le and Nguyen, 2022;Evans and Farrell, 2023;Wu et al, 2023;Sari et al, 2023;Jiang et al, 2023;Simeão and Ferreira, 2023) 5 4 1 5…”
Section: Current Literature On Lean and Covid-19mentioning
confidence: 99%
“…As for "Resilience", research conducted in 2022 regarding the impact of the COVID-19 pandemic in three different companies in the construction industry showed that the companies that were better qualified in relation to Lean principles were also better rated in relation to the dimensions of "Resilience", and, moreover, they had less impact on business and sometimes performed better during the critical period [110]. This result corroborates previous findings (from 2016), which demonstrated the positive synergy between Lean and resilience, and concluded that a company with a high level in implementing the dimensions of resilience and a high breadth in Lean implementation will be more likely to perform better after disruption or a contingency situation [110,111]. In this article, we set out to analyze the relationship between Lean Management and Industry 4.0, exploring how Lean is framed within the so-called 4th Industrial Revolution, and uncovering any remaining opportunities and limitations.…”
mentioning
confidence: 99%